(untitled) - Speight, James G. (Hoboken, New Jersey, 2015)
Introduces the reader to the types of test methods applied to petroleum products, including the need for specifications; Provides detailed explanations for accurately analyzing and characterizing modern petroleum products; Rewritten to include new and evolving test methods; Updates on the evolving test methods and new test methods as well as the various environmental regulations are presented
Keywords: Petroleum products,Sản phẩm dầu khí; Analysis,Phân tích